Hipotireoidismo em cães: aspectos gerais - Freitas, Mateus do Amaral [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
Hypothyroidism is a common endocrine disorder in dogs caused by insufficient production and secretion of thyroid hormones. Most affected dogs have primary hypothyroidism that results from lymphocytic thyroiditis, idiopathic thyroid atrophy, or more rarely, neoplastic destruction. Secondary hypothyroidism resulting from inadequate secretion of thyrotropin (thyroid-stimulating hormone –TSH) from the pituitary gland is less commonly recognized. Tertiary hypothyroidism resulting from a deficiency of hypothalamic thyrotropin-releasing hormone (TRH) has not been documented in dogs. The diagnosis of hypothyroidism in dogs is made on the basis of clinical findings, results of routine laboratory and thyroid gland function tests and response to thyroid hormone replacement. Unfortunately, these tests have high sensitivity, but low specificity, for use in the diagnosis of hypothyroidism. Thyroid hormone supplementation is indicated for the treatment of confirmed hypothyroidism and for the diagnoses of the disease through clinical response to trial therapy

Hipotireoidismo é uma endocrinopatia comum em cães causada por insuficiente produção e secreção de hormônios tireoideos. A maioria dos cães afetados tem o hipotireoidismo primário que resulta da tireoidite linfocítica, atrofia idiopática da tireóide ou, mais raramente, de destruição neoplásica. O hipotireoidismo secundário resultante da inadequada secreção da tireotrofina (hormônio tireotrófico – TSH) pela glândula pituitária é menos reconhecido. O hipotireoidismo terciário resultante da deficiência do hormônio liberador de tiroxina (TRH) pelo hipotálamo não tem sido documentado em cães. O diagnóstico do hipotireoidismo em cães é feito com base nos sinais clínicos, resultados da rotina laboratorial, testes da função da glândula tireóide e resposta a reposição dos hormônios da tireóide. Infelizmente, os testes têm alta sensibilidade mas baixa especificidade para uso no diagnóstico de hipotireoidismo. A suplementação do hormônio tireóideo é indicada para o tratamento do hipotireoidismo confirmado e para tentativa de diagnóstico de hipotireoidismo por meio da resposta clínica à terapia
Keywords: Cão - Doenças - Aspectos endócrinos; Hipotireoidismo; Endocrinologia veterinaria